Gender and Literature: A Feminist Study in A Collection of Short Stories Rokat Tase' by Muna Masyari - Achmad Sudiyono Efendi (Journal Corner of Education, Linguistics, and Literature, 2022)
This study aimed to reveal the gender injustice experienced by female characters using feminism theory, focusing on gender inequality from Mansur Fakih. The object of this research was a collection of short stories Rokat Tase' by Muna Masyari by taking five samples from twenty short stories population. This study uses a qualitative method, namely research that examines the condition of natural objects, where the researcher is the key instrument of the research. This research was a review study. Then to analyze the data, the researcher used the descriptive method. The results of this study indicate that there are gender injustices such as marginalization, subordination, stereotypes, violence, and the workload experienced by female characters in Muna Masyari's collection of short stories Rokat Tase. In addition, there are traditions and rules in the household and the domination of men over women, which causes women to be powerless.